SAT0095 Leucine-Rich Alpha2-Glycoprotein Is A Useful Biomarker To Evaluate The Clinical Disease Activities of Rheumatoid Arthritis under Treatments. (15th July 2016) - Hosono, Y.; Hashimoto, M.; Fujimoto, M.; Serada, S.; Furu, M.; Ito, H.; Terao, C.; Yamamoto, W.; Fujii, T.; Mimori, T.; Naka, T.
Abstract : Background: Acute phase biomarkers such as erythrocyte sedimentation rate (ESR) and C-reactive protein (CRP) are usually used for the evaluation of the disease activity of rheumatoid arthritis (RA). However, these biomarkers are sometimes not useful in evaluating the disease activity of RA patients in daily clinical practice, because they often become within normal range after the initiation of treatments. Thus, new biomarker which reflects the disease activity of RA under the treatment is required. Leucine-rich-α2-glycoprotein (LRG) is a newly identified biomarker that reflects inflammation and is correlated with the 28-joint Disease Activity Score even in patients treated with IL-6 receptor antagonist. Objectives: To assess whether serum LRG levels could be a biomarker to evaluate the disease activity of RA under treatments in daily clinical practice. Methods: Serum LRG levels were measured by enzyme-linked immunoabsorbant assay in 370 consecutive RA patients who were under treatments in our facility in 2012. Disease activity was evaluated by Clinical Disease Activity Index (CDAI) that does not include ESR or CRP as components. Radiological joint destruction was evaluated by modified Total Sharp Score (mTSS). Multivaiate analysis of covariance (MANOVA) was used to assess the association between CDAI and LRG, ESR, CRP levels and the association between mTSS and LRG, ESR, CRP, disease duration, and anti-CCP antibody level. Results: Among 370 patients, 71% were treated by methotrexate and 29% by biological DMARDs and average CDAI was 7.8±6.2 (low disease activity). After MANOVA analysis, LRG but not ESR or CRP showed the significant correlation with CDAI (LRG; effect size 0.034, p=0.0007, CRP; effect size 0.010, p=0.055, ESR; effect size 0.0053, p=0.18). LRG significantly correlated with the disease activities in RA patients, even when ESR or CRP levels were within normal range. In addition, LRG showed the significant correlation with mTSS as well as disease duration and anti-CCP antibody level (LRG; effect size 0.019, p=0.017, disease duration; effect size 0.769, p<0.001, and anti-CCP antibody; effect size 0.036, p=0.0011), while ESR and CRP did not (ESR; effect size 0.0038, p=0.28, CRP; effect size 0.00073, p=0.64). Conclusions: LRG is useful marker to evaluate the disease activity and to estimate the joint damage of RA patients under treatments in daily clinical practice independent of CRP and ESR levels. Disclosure of Interest: None declared